Social Media Efficacy on Prevention and Control of Covid-19 Pandemic in Ilorin South Local Government Area, Kwara State - Abubakar Dare Baba (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study investigated social media efficacy on prevention and control of Covid – 19 pandemic in Ilorin South Local Government Area, Kwara State. This study examine effectiveness of awareness created by the Facebook, NCDC messages and Twitter on prevention and control of Covid – 19 pandemic in Ilorin South LGA, Kwara State. The study adopted descriptive research design of survey type. A multi-stage sampling technique of stratified and purposive techniques was employed to select 150 respondents for the study. A researchers structured questionnaire validated and pilot tested with the use of test re-test reliability method and 0.75r were obtained. The findings revealed that awareness created through facebook, NCDC and Twitter have much impacts on prevention and control of Covid – 19 pandemic. Based on this findings, the study recommends that health officers should encourage people on the needs to use social media tools like facebook, NCDC messages, Twitter, Youtube and soon to gain insight on prevention and control of Covid – 19 pandemic.